Evaluation of Lighting and Power Systems At State Vocational School 1 Kramatwatu - Kautsar, Alif; Irwanto, Irwanto; Fatkhurrokhman, Mohammad (Sainteks: Jurnal Sain dan Teknik, 2024)
Evaluation of the electrical installation of a building is something that needs to be done so that the quality of the electrical installation remains in good condition and reliability. This research aims to evaluate the lighting system. Energy needs are currently playing an increasingly important role in human life, one of which is the problem that arises in the use of energy consumption in the New Classroom Building (RKB) at SMK Negeri 1 Kramatwatu. This research aims to determine the value of energy requirements in the RKB building (IKE, kWh , kVA and Cost Tariff), the RKB building is a building that has 2 floors with a total of 12 classrooms, this building was established at the end of 2023, the RKB building has never had an Energy Audit which is useful for identifying inefficient energy use, this energy audit can reduce energy use in order to increase the level of efficiency. To find out the results with data that has been collected using manual calculations and lighting simulations using DIALux software version 12.1. This RKB building uses energy of 17,154kWh/day, 85,770kWh/week, 343,080kWh/month and 4,322,960kWh/year. 226,925VA/Day, 1,134,625VA/Week, 4,538.5VA/Month and 54,462VA/Year. and customer rates Rp. 19,061;/Day, Rp. 95,308;/week, Rp. 381,234;/Month and Rp. 4,574,808;/Year on consumption of lighting power loads and other power loads.